MULTIDIMENSIONAL APPROACH TO THE SENSITIVITY ANALYSIS OF INNOVATIVE PROJECTS RISK ASSESSMENT - A. M. Pokrovskiy (Стратегические решения и риск-менеджмент)
Article is devoted to a multidimensional approach to an important part of risk analysis of innovative projects – evaluation of the sensitivity of risk when you change their underlying caus-es. Proposed and tested on a concrete example method of forming an empirical base for modeling the sensitivity of risk evaluations of innovative projects within that do not violate the consistency of the matrix of paired statements. It is shown that this can be obtained economically significant results, including assessment of priority areas of investment elasticity of the weights of different types of risks, and identifying the most sensitive risk factors.